Resolving leukemic stem cell heterogeneity and plasticity with single-cell multiomics - Huang, Frank Y.; Trumpp, Andreas; Stelmach, Patrick (Seminars in hematology, 2025)
Acute myeloid leukemia (AML) is an aggressive blood cancer in which disease initiation and relapse are driven by leukemic cells with stem-like properties, known as leukemic stem cells (LSCs). The LSC compartment is highly heterogenous and this contributes to differences in therapy response. This heterogeneity is determined by genetic and nongenetic factors including somatic mutations, the cell of origin, transcriptional and epigenetic states as well as phenotypic plasticity. While this complicates the identification and eradication of LSCs, it also presents an opportunity to tailor therapeutic strategies to the phenotypic and functional states of LSCs present in a patient, exploiting their specific vulnerabilities. The emergence of single-cell multiomics technologies has transformed our ability to dissect cellular heterogeneity in AML, enabling simultaneous interrogation of genomic, transcriptomic, epigenomic and proteomic layers and providing high-resolution molecular snapshots of individual cells. In this review, we discuss causes and consequences of LSC heterogeneity, highlight advances in single-cell multiomics technologies to resolve it and outline how they can address shortcomings in our understanding of LSC heterogeneity and plasticity to revolutionize diagnostics and disease monitoring of AML.
Online verfügbar: 5. August 2025, Artikelversion: 13. November 2025
Gesehen am 27.01.2026